Impaired transport of mitochondrial transcription factor A (TFAM) and the metabolic memory phenomenon associated with the progression of diabetic retinopathy. Issue 3 (11th March 2013) - Santos, Julia M.; Kowluru, Renu A.
Abstract Background Diabetes damages retinal mitochondrial DNA (mtDNA) and compromises the mtDNA transcription. In the transcription and replication of mtDNA, nuclear‐encoded mitochondrial transcription factor A (TFAM) is considered a key activator. We have shown that in diabetes, although retinal TFAM gene expression is increased, its mitochondrial levels are decreased. This study investigates the role of mitochondrial outer and inner membrane transport systems in the transfer of TFAM into the mitochondria in diabetes and how reversal of hyperglycaemia affects the ability of TFAM to reach the mitochondria. Methods Components of the membrane transport system, Tom70, Tom40, Tim23, and Tim44, were analysed in the retina from streptozotocin‐induced diabetic rats maintained in poor control or in good control for 8 months, or in poor control for 4 months followed by in good control for 4 months. The binding of TFAM with Tom70 and Tim44 was determined by co‐immunoprecipitation and that with mtDNA by chromatin immunoprecipitation. Results Retinal expressions of Tom70, Tom40, and Tim44 were significantly decreased in diabetes, and the binding of TFAM with Tom70, Tim44, and mtDNA was impaired. Reversal of hyperglycaemia had no beneficial effect on the decreased binding of TFAM to Tom proteins and mtDNA. Conclusions Thus, subnormal membrane transport to systems in diabetes impair the transfer of TFAM into the mitochondria, and decreased TFAM–mtDNA binding that results in subnormal mitochondria transcription. These processes continue to be dysfunctional even after the hyperglycaemic insult is terminated. Strategies targeting mitochondrial membrane transport proteins could have the potential of improving mitochondrial biogenesis and slowing or halting the progression of diabetic retinopathy. Copyright © 2012 John Wiley & Sons, Ltd.